Analyzing the subscription based download service application as a part of 3G content delivery solution : A case study for Celcom (M) Bhd / Sharifah Nurul Iza Saiyid Kushari - Saiyid Kushari, Sharifah Nurul Iza (2003)
Third Generation wireless technology or 3G brings together two of the world's fastest growing industries; mobile communication and wireless internet. Subscription Based Download Service (SBDS) is a type of 3G service that focuses on video downloads and large files content. It serves as a solution for the weakness of current downloading service. SBDS has a download feature whereby the content being pushed to subscriber during off peak hours. Compared to user initiated downloading, network gets congested most of the time due to unscheduled request of content. The protocols involved can only support small sized files content and lacks of recoverability. Downloading needs to be initiated all over again if interruption does occur. Flexibility is the key feature of the SBDS. Furthermore, this research also aims to analyze the SBDS concept and also the interdependencies of the entities involve in the content based service value chain. It analyzes all aspects of the system including the Over-The-Air protocol for downloading, business models and roles of entities. It exposes how content provisioning works and answers why it is significant to emphasize on content market and services. The research is done based on the collection of primary data from interviews held with Celcom (M) Berhad personnel. The secondary data consists of previous studies, newspapers and journals related to the topics. Subsequently, the research also discovers the challenges and issues surrounding 3G multimedia content management and content based services. Finally the research provides recommendations to overcome the problems in 3G environment.